Effectivity of Acupressure in Low Back Pain - Indri Seta Septadina (HM Publisher, 2021)
Low back pain is defined as located pain and discomfort below the costal margin and above the superior gluteal line, with related pain in the lower limb, and repeated incorrect posture of work activities that demand effort with excess of flexion, rotation, vibration on the chest and carrying weight, being chronic if its persists for three months or more. This research aimed to find out the efficacy of accupressure on Dachangshu, Shenshu, and Yaoyangquan points using pretest-posttest group design by comparing the mean decrease in pain threshold, RMDQ and Test Straight Leg between control using Dingchuan and Waihuaijian points and therapy group using Shenshu, Dachangshu, and Yaoyangquan acupoints twice a day with paired T test formula. The mean decreased in pain threshold VAS, RMDQ and Test Straight Leg obtained form therapy group toward 16 elderly above 45 years for 4 weeks showed that there is a significant result (p=0,000). In conclusion, accupressure therapy using Dachangshu, Shenshu and Yaoyangquan can be used to treat low back pain.